Top3 Processes Recombination Intermediates and Modulates Checkpoint Activity after DNA Damage - Mankouri, Hocine W. (The American Society for Cell Biology, 2006)
Mutation of TOP3 in Saccharomyces cerevisiae causes poor growth, hyperrecombination, and a failure to fully activate DNA damage checkpoints in S phase. Here, we report that overexpression of a dominant-negative allele of TOP3, TOP3(Y356F), which lacks the catalytic (decatenation) activity of Top3, causes impaired S-phase progression and the persistence of abnormal DNA structures (X-shaped DNA molecules) after exposure to methylmethanesulfonate. The impaired S-phase progression is due to a persistent checkpoint-mediated cell cycle delay and can be overridden by addition of caffeine. Hence, the catalytic activity of Top3 is not required for DNA damage checkpoint activation, but it is required for normal S-phase progression after DNA damage. We also present evidence that the checkpoint-mediated cell cycle delay and persistence of X-shaped DNA molecules resulting from overexpression of TOP3(Y356F) are downstream of Rad51 function. We propose that Top3 functions in S phase to both process homologous recombination intermediates and modulate checkpoint activity.